(untitled) (CIPEEX, 2026)
Introduction: The Human Immunodeficiency Virus (HIV) directly attacks the immune system, which functions as the body’s protective shield against diseases, weakening its defenses and making the organism more susceptible to various infections and tumors. Considering that the COVID-19 pandemic posed a significant challenge to the continuity of HIV care, it becomes crucial to analyze its impact on the epidemiological profile of the infection in the municipality of Anápolis. Objective: The central objective of this project is to describe and compare the clinical and epidemiological characteristics of new HIV cases in the post-pandemic period (2023–2024) with those in the pre-pandemic period (2018–2019), in order to assess whether significant changes occurred in the socio-epidemiological pattern of cases in the municipality. Methodology: The methodology will consist of an observational, cross-sectional study with a quantitative approach, both retrospective and prospective in nature, using as sources the compulsory notification forms from the National System of Notifiable Diseases (SINAN) and data from DATASUS. Results: Data analysis will support the development of more effective and targeted public policies, based on a Detailed Action Plan focused on improving prevention, diagnosis, treatment, and quality of life for people living with HIV. Conclusion: This study represents a crucial step in the fight against HIV in Anápolis, as by unveiling the post-pandemic epidemiological scenario and outlining possibilities for public interventions, it contributes to building a future free of the disease in the city.